2022
DOI: 10.3390/ijerph19031184
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular System during SARS-CoV-2 Infection

Abstract: SARS-CoV-2 virus can not only damage the respiratory system but may also pose a threat to other organs, such as the heart or vessels. This review focuses on cardiovascular complications of COVID-19, including acute cardiac injury, arrhythmias, biomarkers, accompanying comorbidities and outcomes in patients diagnosed with SARS-CoV-2 infection. The research was conducted on the databases: PubMed, Springer, ScienceDirect, UpToDate, Oxford Academic, Wiley Online Library, ClinicalKey. Fifty-six publications from 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
(356 reference statements)
0
4
0
3
Order By: Relevance
“…Identifying the primary processes responsible for the abnormalities in gas exchange and respiratory mechanics, as well as their variations over time, should determine the best configuration of respiratory support. Monitoring inspiratory effort in spontaneously breathing patients (non-invasive or invasive ventilation) is an essential supplementary tool for informing the decision of mechanical support and identifying treatment failure [ 19 ]. Clinical, physiological, and radiological surveillance and early referral to a chest specialist are currently advised for all COVID-19 survivors [ 6 ].…”
Section: Sars-cov-2 and Respiratory Systemmentioning
confidence: 99%
“…Identifying the primary processes responsible for the abnormalities in gas exchange and respiratory mechanics, as well as their variations over time, should determine the best configuration of respiratory support. Monitoring inspiratory effort in spontaneously breathing patients (non-invasive or invasive ventilation) is an essential supplementary tool for informing the decision of mechanical support and identifying treatment failure [ 19 ]. Clinical, physiological, and radiological surveillance and early referral to a chest specialist are currently advised for all COVID-19 survivors [ 6 ].…”
Section: Sars-cov-2 and Respiratory Systemmentioning
confidence: 99%
“…O organismo em resposta a agressão viral apresenta um estado inflamatório persistente que incluem: alterações plasmáticas (sistema complemento, coagulação/fibrinólise e cininas), gerados pelas células (citocinas, mediadores lipídicos, oxidantes, proteases, óxido nítrico e neuropeptídeos) e indução de síntese proteica, um estágio precoce na produção de citocinas. Esses fatores são considerados responsáveis pela injúria celular e alterações no surfactante, com distúrbio da relação ventilação/perfusão, resultando em hipoxemia (Kozlik, et al, 2022).…”
Section: Resultsunclassified
“…As células cardíacas que expressam receptores ECA2, envolvem o endotélio da microcirculação e estão envolvidas na integridade da parede dos vasos que irrigam o miocárdio. Ao serem danificadas pela infecção viral, estas são preparadas para liberar uma série de fatores de crescimento que tentam restaurar a integridade microvascular, esses fatores contribuem para a inflamação do tecido local, perturbando a eletrofisiologia celular atrial (Kozlik, et al, 2022).…”
unclassified
“…However, these chips are not the only ones used for research on viral diseases. Given that COVID-19, as well as other coronaviruses, can affect several organs, including kidneys, and the gastrointestinal, cardiovascular and nervous systems [ 90 , 91 , 92 , 93 ], 3D models of other organs have been used. Bein et al [ 94 ] recently modeled an immunocompetent human Intestine-on-a-Chip to study enteric NL63 coronavirus infection and treatment, whereas Helms et al [ 95 ], using kidney organoids derived from pluripotent stem cells, showed that SARS-CoV-2 can directly infect and damage kidney tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%